The comparative study of temperature rise, time consuming and cut quality among piezosurgery, conventional rotary instruments and Er: YAG laser in apicectomy - Li-Yuan Qi; Rui Zhang; Juan Zhang; Jia-Sha Wang; Ji Wang; Ruo-Xi Liu; Yu Jin; Jing Zhao (BMC, 2024)
Abstract Objectives This study aimed to compare the temperature rise, time consuming and cut quality of apicectomy using three different methods. Materials and methods Twenty-four single-rooted teeth were collected and divided into four groups operating apicectomy with a NINJA tip of a piezoelectric device (G1), a diamond bur with 300,000 rpm (G2), and Er: YAG laser at 200 mJ/ 30 Hz (G3) as well as 250 mJ/ 30 Hz (G4). The temperature elevation and time were recorded and the cut quality was evaluated via stereomicroscope and scanning electronic microscopy (SEM). Results The temperature increases for G1 was significantly higher than for G2. However, there was no significant difference between G1 and G2 with laser groups respectively. The median time for apicectomy was: 100.14s for G1, 22.65s for G2, 33.58s for G3, and 21.80s for G4. G1 is the most time-consuming group and there was no statistically significance in the comparisons with G2, G3 and G4. Cut quality was assessed by crack occurrence, smear layer formation and dentinal tubules exposed. The percentage of cracked teeth in G1 and G2 was 33.33% and for laser groups the percentage was 16.67% each. SEM showed that no smear layer formed and almost all dentinal tubules were exposed on resected surfaces for G3&G4, surfaces from G2 were partly covered by smear layer, and surfaces from G1 were fully covered by smear layer and with no dentinal tubules exposed. Conclusions Er: YAG laser and conventional rotary instruments were safe and efficient for apicectomy and with a better cut quality when compared with piezoelectric equipment. Er: YAG laser could be a promising technique for apicectomy and further studies are necessary, especially larger sample in vivo investigations, to verify the feasibility of Er: YAG laser in endodontic surgery.